David Davis papers - Davis, David, 1815-1886.
Correspondence of Davis addressed to his brother-in-law, Julius Rockwell, relating to political and social issues of the period. Davis discusses subjects such as Abraham Lincoln, African American social and political rights, the Civil War, Andrew Johnson and the impeachment proceedings, Reconstruction, and slavery. Other subjects include elections, national politics, issues before Congress, matters under consideration by the U.S. Supreme Court, and family affairs including travels in the South.
U.S. Supreme Court justice and U.S. senator from Illinois.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Johnson, Andrew, -- 1808-1875.; Johnson, Andrew, -- 1808-1875 -- Impeachment; Lincoln, Abraham, -- 1809-1865.; Rockwell, Julius, -- 1805-1888 -- Correspondence; Davis family; United States. -- Congress; United States. -- Supreme Court; African Americans -- Civil rights; African Americans -- Social conditions; Constitutional law -- United States; Elections -- United States; Law -- United States; Reconstruction (U.S. history, 1865-1877); Slavery -- United States; Southern States -- Description and travel; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 19th century; United States -- Social conditions -- 19th century; Jurists; Senators, U.S. Congress -- Illinois